DEVELOPMENT OF THE EURASIAN ECONOMIC UNION IN THE CONTEXT OF INTERNATIONAL CHANGES - Borsch, Lyudmila; Tsohla, Svetlana; Simchenko, Nataliia; Reznikova, Olga; Burkaltseva, Diana; Gerasimova, Svetlana; Abibullayev, Memet; Bamatov, Ibragim (Revista Inclusiones, 2019)
The aim of the article is to assess the level of integration processes in the Eurasian Economic Union (EAEU) in the process of forming a common market considering changes in the international arena. The article provides a theoretical analysis of the integration approach in the functioning of the EAEU management system and considers integration processes in the financial sector, infrastructure, as well as trade and technological processes of the EAEU member countries. The authors have revealed the characteristic features of the development of the socio-economic system of the EAEU member countries, as well as differences between the countries. The prospects for the development of the EAEU domestic market have been shown and an evolutionary model for its modernization has been built. Based on the results of the study, it has been concluded that in modern conditions, in the era of digital technology, evolutionary modernization is inevitable. On its basis, integration processes in all areas of the developing economic market are improved.